Perceptions of Farmers on Resilience to Stress: A Study in Rajasthan - G. Jaya; K.C. Gummagolmath; Phand, Shahaji; Kumar, G . Dileep (Journal of Agricultural Extension Management, 2020)
In the Indian context, farmers constantly undergo occupational stress due to frequent drought, erratic rain fall, non-availability of timely agricultural inputs, agricultural loans etc. In this context, a study was conducted to understand the perceptions of the farmers and how they cope up with the stress and what factors contribute to relieve the stress. The study was conducted in Dausa and Tonk districts of Rajasthan state. A total of 202 farmers were interviewed and their responses are analyzed using descriptive and factor analysis techniques. A total of six factors are successfully constructed using factor analysis and the factors are named as 1. Agriculture activities that supplement additional income 2. Social Factors 3. Factors related to family 4. Religious factors 5. Cultural factors 6. Health factors. The results show that several factors are responsible for reduced stress. Which included farmers welfare schemes, funny moments, love from family members going to pilgramages and good health